Ten adverse outcomes when manager focus on creating shareholder value: a review - Di Miceli da Silveira, Alexandre (Review of Global Management, 2020)
This paper surveys the literature criticizing the view that managers should run companies aiming to create shareholder value by maximizing stock prices. Based on a multidisciplinary approach, I include empirical and theoretical papers from fields such as corporate law, management, finance, economics, business ethics, social psychology, and sociology of organizations. Ten main harmful effects from the adoption of the shareholder value paradigm stand out. I also add to the literature by presenting anecdotal evidence through short business cases illustrating these adverse outcomes. Together, this growing literature provides compelling evidence that governing companies in order to maximize current stock prices might lead to severe negative consequences for all corporate constituencies, including society and shareholders themselves.